EMPLOYEE PERFORMANCE: SERVANT LEADERSHIP AND PERSONNEL COMMITMENT - Dadang, Dadang; Megaster, Tekni; Rofiq, Iwan Setiawan (Univesitas Muhammadiyah Tangerang, 2023)
This study aims to determine the contribution of servant leadership and personnel commitment to employee performance at PT. The true dynamic partners of the Independent Variables are servant leadership and personnel commitment while the dependent is employee performance. This study used a quantitative approach. The sample used in this study was 55 respondents using a random sampling method from a population of 55 workers at PT. True Dynamic Partners. Primary data collection was obtained from distributing questionnaires and secondary data was obtained from agencies. The results of this study show that Servant Leadership (X1) and Personnel Commitment (X2) make a positive contribution to employee performance (Y) at PT Mitra Dinamika Sejati. Servant Leadership and Personnel Commitment together contribute to employee performance. Keywords: Servant Leadership, Personnel Commitment, Employee Performance.